Human Resource Development Strategy in Facing the Challenges of Business Globalization - Resdi Enzelina Br Tampubolon (Cattleya Darmaya Fortuna, 2024)
This study aims to analyze human resource (HR) development strategies in facing the challenges of business globalization. Globalization demands organizations to have competent, adaptive HR who are able to compete internationally. This study uses a quantitative approach with descriptive and verification methods. Data were collected through questionnaires distributed to employees in globally oriented companies using simple random sampling techniques. Data analysis was conducted using multiple linear regression. The results show that HR development strategies consisting of training and development, digital competence, and global cultural adaptation have a positive and significant effect on organizational readiness in facing business globalization, both partially and simultaneously. The training and development variable is the most dominant factor. The coefficient of determination value of 0.68 indicates that 68% of organizational readiness is influenced by HR development strategies. The conclusion of this study confirms that HR development is a key factor in increasing organizational competitiveness in the era of globalization. Therefore, organizations need to optimize training programs, improve digital competence, and build an adaptive and globally oriented work culture.